Literature Review: Winogradsky Column sebagai Metode Biologis untuk Degradasi Masker Medis (Disposable Mask) - Tahri; Savira Hidayanti; Nafi Atul Ummah; Yusri Septiana; Anugrah Dhuhana Yusuf (Universitas Nusantara PGRI Kediri, 2023)
The Covid-19 pandemic has had many negative impacts on human life. One of them is the large amount of medical mask waste. The purpose of this article is to collect and analyze articles regarding the use of the Winogradsky column in the degradation of plastic waste and medical masks. The method used in making this article is a review article. The articles used are relevant research articles from the last 10 years. After conducting research on the article, it was concluded that the decomposition of plastic waste using the Winogradsky column method proved successful in reducing the quality of polyethylene